Apponyi Albert kultuszának második felvonása: A 80. születésnap - Anka, László (Közép-Európai Közlemények, 2023)
The glorification of Count Albert Apponyi began with the mission of the Hungarian peace delegation in 1920 and arose out of a need to revise the Treaty of Trianon. Thus, in the history of venerated Hungarian statesmen, he belongs in the chapter dedicated to revision. In an earlier work, the author described in detail how Count Albert Apponyi’s seventy-fifth birthday had been celebrated across the nation in 1921. Count of Nagyappony Albert Apponyi (1846–1933) turned eighty on May 29th, 1926. Hungary was prepared to celebrate the jubilee birthday of the elderly aristocrat. The National Assembly, the General Assembly of Budapest, the various organizations (the Hungarian Foreign Policy Association, the National Stefánia Alliance, the Policlinic Society of Budapest and the Saint Stephen Academy) of which Apponyi was the head and numerous of his admirers who filled major positions in public life all began to organize. However, one month before his birthday, Albert Apponyi wrote a letter to the Speaker of the National Assembly requesting that the Hungarian people forgo the celebration and allow him to spend his birthday in the quiet company of his family. His request was only partially fulfilled. The jubilee celebration went on in his absence while only a few delegations disturbed him on his countryside retreat. The current study presents the preparations for the celebration of the missing Count, the various birthday gifts that he received, the manner in which he was venerated and how all of these conformed to his concept and propaganda of revisionism.